Effects of Strike Action on Teaching and Learning Effectiveness Among Public Secondary School Students in Anambra State (Integral Research, 2025)
This paper investigates the effects of strike action on teaching and learning effectiveness among public secondary school students in Anambra State.  To accomplish this, four research questions were formed.  The method used in carrying out the research is by administration of questionnaires.  The calculation of the study consisted of 23 public secondary schools in Aguata L.G.A. The sample size used was 300 and comprising of 270 students and 30 teachers from the public secondary schools in Aguata L.G.A. using a simple random sampling technique.  The responses to the questionnaire were analyzed and the following findings were made. Strike action is caused by non-payment of salaries and other allowances, insensitive to the welfare of staff etc. Strike affects the academic standard of the students as well as lead to poor academic performance of the students. Strike affects the actualization of educational goal by affecting the educational development in secondary school. The incessant strike actions in secondary schools could be averted if the following measures were adopted; use of dialogue, making consistent policies and government being sensitive to the plight of staff. Based on the above finds, recommendations were made and conclusions drawn.
Keywords: Strike/Industrial Action, Victimization of workers, Anambra State, Secondary School Students, academic standard.